Experimental Proof of Spin Influence on Rail-Wheel Contact Forces: Measurements Design on Roller Test Rig (Current Problems in Rail Vehicles, 2025)
For assessment of an influence on contact forces distribution in rail-wheel contact a roller test rig is going to be used – Railway Wheel Test Rig (RWTR), which is located in the authors’ workplace. RWTR approximates conditions in rail-wheel contact with contact geometry, magnitude of wheel forces, rotational velocity, angle of attack. For the designed experiments, an augmentation of the installed measuring system is required. This paper deals with an analysis of requirements for designed experiments of spin influence and with a complex revision of a current measuring system of all quantities on RWTR. From this analysis we conclude measurement modifications, mainly with respect to the rollers’ relative position.
Keywords: rail-wheel contact; adhesion; spin creepage; roller test rig; measuring system